Our (Museum) World Turned Upside-Down: Re-Presenting Native American Arts - Phillips, Ruth B.; Berlo, Janet Catherine (College Art Association, 2007)
Berlo and Phillips discuss the quantities and relevance of Native American art objects in public and private collections, how they are displayed, as well as some examples of how museums acquired Native art objects. The authors suggest a need to re-evaluate how Native art objects are displayed in institutional settings, and they situate their argument within the ongoing debate about repatriation of native art objects currently owned by institutions.